Warpage in wafer-level packaging: a review of causes, modelling, and mitigation strategies - Praful, Pallavi; Bailey, Chris (Frontiers in Electronics, 2025)
Wafer-level packaging (WLP) is a pivotal semiconductor packaging technology that enables heterogeneously integrated advanced semiconductor packages with high-density electrical interconnections through its efficient and highly reliable manufacturing processes. Within this domain, fan-out wafer-level packaging has gained prominence due to its potential for high integration capacity, scalability, and performance on a smaller footprint. This review examines FOWLP technology and its associated challenges, primarily warpage. As semiconductor companies strive to develop cutting-edge packages, wafer warpage remains an intrinsic and persistent issue affecting yield and reliability at both the wafer and package levels. Warpage characterization techniques and modeling approaches, including theoretical, numerical, and emerging artificial intelligence and machine learning (AI/ML) methods, have been analyzed. The structural parameters and properties of the constituent materials of the reconstituted wafer and the FOWLP process have been considered to evaluate the effectiveness of these methods in predicting and analyzing warpage. Potential directions and limitations in warpage prediction and mitigation have been outlined for future research for more reliable and high-performance FOWLP solutions.